Procedurally just organizational climates improve relations between corrections officers and incarcerated individuals - Peterman Evans, Danieli (Psychology, crime & law, 2021)
Correctional officers’ attitudes about the treatment of inmates can affect an inmate’s experience within a correctional institution. Previous research, largely outside correctional settings, suggested that individual (e.g. personality traits; racial bias) and organizational (e.g. procedural justice; training) factors related to attitudes regarding inmates. However, research involving correctional officers has been limited. In a sample of correctional officers (N = 89), we collected self-report measures of punishment-oriented attitudes, individual (personality traits, racial bias), and organizational (procedural justice in the work environment) factors. Agreeableness, a personality trait, and procedural justice in the work environment were significantly negatively associated with punishment-oriented attitudes, whereas racial bias was significantly positively associated with these attitudes. Furthermore, correctional officers who worked on a new rehabilitation-focused unit had higher perceptions of procedural justice in their work environment, and this was associated with more positive attitudes toward inmates. The present study provided preliminary evidence that both individual and organizational factors were important to consider within a correctional setting, but that instituting a procedurally just culture in the prison could promote more humane attitudes toward those currently incarcerated.